2010
DOI: 10.1002/jor.21251
|View full text |Cite
|
Sign up to set email alerts
|

Porous tantalum stimulates the proliferation and osteogenesis of osteoblasts from elderly female patients

Abstract: Porous tantalum (Ta) implants have been successful in various orthopedic procedures for patients with compromised boneforming abilities. Previous studies demonstrated that human osteoblast (HOB) cultures from older female patients produced less bone on implant materials in vitro compared to HOBs from age-matched male and younger female patients. In this study, the responses of HOBs from younger (<45) and older (>60 years old) female patients were compared on Ta, titanium fiber mesh (TFM) and tissue culture pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 42 publications
4
68
1
2
Order By: Relevance
“…9 Porous Ta is non-toxic, highly corrosion resistant, biocompatible, and bioactive; 10 it allows both bone ingrowth and ongrowth and promotes osteogenesis to establish osseointegration and osseoincorporation, thus significantly enhancing the initial stability of implants 9,11 and the applicability to osteo-regenerative strategies. 12 Currently, porous Ta has been widely applied in orthopedic applications and oral implants, and studies have shown that it can highly promote the adhesion, proliferation, differentiation, and mineralization of osteoblasts in vitro 3,13,14 and in vivo. 15,16 In addition, recent studies have revealed that porous Ta combined with bone marrow stromal stem cells (BMSCs), 17 bone marrow mesenchymal stem cells (BMMSCs), 18 and fibrin 19 can better promote cell proliferation, bone integration, and regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…9 Porous Ta is non-toxic, highly corrosion resistant, biocompatible, and bioactive; 10 it allows both bone ingrowth and ongrowth and promotes osteogenesis to establish osseointegration and osseoincorporation, thus significantly enhancing the initial stability of implants 9,11 and the applicability to osteo-regenerative strategies. 12 Currently, porous Ta has been widely applied in orthopedic applications and oral implants, and studies have shown that it can highly promote the adhesion, proliferation, differentiation, and mineralization of osteoblasts in vitro 3,13,14 and in vivo. 15,16 In addition, recent studies have revealed that porous Ta combined with bone marrow stromal stem cells (BMSCs), 17 bone marrow mesenchymal stem cells (BMMSCs), 18 and fibrin 19 can better promote cell proliferation, bone integration, and regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous studies employed Ta and Ti samples on specific surface structures such as those with relatively high roughness (Ra = 0.29-0.37 mm) [3], nanostructure (nanotube of 100 nm in diameter and 300 nm in height) [13], and porous structure (pore size of 400-600 mm and porosity of approximately 80%) [14]. Since these structural properties will inevitably affect the osteoblastic differentiation of adherent cells [15][16][17], the osteoinductive performance associated with the inherent chemical properties of the two materials may be masked.…”
Section: Introductionmentioning
confidence: 99%
“…13 Sagomonyants KB and Welldon KJ, respectively, reported that porous tantalum stimulated the proliferation and osteogenesis of osteoblasts from elderly women patients and from patients with total joint replacement surgery. 14,15 Porous tantalum medical product made by Zimmer corporation in the USA has been successfully applied to the hip, knee, shoulder, ankle joint, and the spinal surgery. [16][17][18][19][20][21] Nevertheless, melting point of tantalum is about 3000 C, so porous tantalum with highly interconnected pores and uniform honeycomb structure is very difficult to obtain through the traditional technology.…”
Section: Introductionmentioning
confidence: 99%